The Management of Karnashula (Otalgia) with Fresh Paribhadra Patra Swarasa Karnapurana (Ear Drop) in Karnasula with or without Irimedadi Taila Gandusham (Gurgle) - Sreenivasulu Murari,; Khatun Hazera, (International Journal of Ayurveda and Pharma Research, 2022)
Karnashula (otalgia) is described under Karnaroga. Karna is the seat of Shravanendriya, made by Panchamahabhuta predominantly Akash mahabhuta and it is concern for Shabda. Karnashool is mentioned as the separate disease entity but and also one of the features of ear diseases. Mature Paribhadra leaves which is mentioned in Bhavaprakash used for Karna purana as a Swarasa form. Irimedadi Taila which is also mentioned in Bhavaprakash used for Gandusha as it has Krimihara and Vranaropana property. This study is a contributing to the clinical usefulness of Paribhadra patra swarasa Karnapurana in Karnasula with or without Irimedadi taila gandusham. (gargle)Methodology: In this comparative study Paribhadra patra swarasa karnapurana (ear drop) in Karnasula with or without Irimedadi taila gandusham. 40 patients of Otalgia (Karnashula) were randomly selected and divided to two groups of 20 patients each. Group A was treated with the ear 6 drops of Paribhadra Patra Swarasa Karnapurana and Group B was treated with ear drops Paribhadra patra swarasa karnapurana in Karnasula with Irimedadi Taila Gandusham.Observations: It was observed in the present study that Group A showed better results in reducing the symptoms of Karnasula when pain (Atiruka) is main symptoms. Re-occurrence of symptoms was merely less in Group A patients compared to Group B patients. Whereas in Group B, Karnasula along with Mukha roga, Kantha roga etc are best responded with Karnapurana along with Irimedadi Taila Ganduham.Conclusion: Ayurvedic medicines are potent enough to manage and reduced recurrence of acute otalgia. The selection of medicine and therapy like Karnapurana and Gandusha and depend on sign and symptoms of the patients. Paribhadra Patra Swarasa and Irimedadi taila both are effective to manage Karnasula. Karnapurana alone is sufficient to manage Karnasula but when it is associated with Mukahroga, Kantharoga then Karnapurana along with Gandusham are choice of treatment.